STRATEGI PENGEMBANGAN PEMASARAN “LAKSA TANGERANG” SEBAGAI SALAH SATU PRODUK WISATA KULINER DI TANGERANG - Dhian Tyas Untari Tyas Untari; Budi Satria (Business Management Journal, 2017)
Laksa Tangerang is one exclusive culinary of Tangerang which has potential to be developed as culinary tourism product. Tangerang considering that tourism sector is one of sector that has large enough of foreign exchange earninge even for regional development level or national development level. This research use IF/EF and SWOT Analisys by using primary data obtained from interviews and observations on culinary entrepreneurs and craftsmen and secondary data from related institutions. Through the analisys a marketing strategy in developing laksa Tangerang and is expected to make recommendations in the development of culinary tourism in Tangerang Melalui analisis tersebut diharapkan penelitian dapat menghasilkan sebuah strategi pemasaran dalam mengembangkan laksa Tangerang dan diharapkanju dapat menjadikan rekomendasi dalam pengembangan wisata kuliner di Tangerang.